Urban sediment in infiltration wells: A lesson from the northern area of greater Yogyakarta city - Slamet Suprayogi; Sudarmadji Sudarmadji; Muhammad Ngainul Malawani (Indonesian Journal of Geography, 2019)
The development of housing in Yogyakarta eventually led to increased levels of runoff. To mitigate runoff increases, infiltration wells were constructed in a specific network. The northern part of Yogyakarta is now facing urbanization, and there are many housing blocks that are being constructed complete with the runoff drainage system. This study aims to reveal the role of the infiltration wells network about runoff and its effectiveness concerning the sediment load in the urban area. The drainage networks in the research area function as a watershed, but not with a single outlet. The runoff flow was spreading through the drainage system and did not accumulate on the single outlet. It can be seen that some infiltration wells supposed as a well, which is a place of accumulation of runoff and sediment.  Most of the infiltration wells have been filled with sediment up to over a quarter, or even more than half, of their carrying volume. Granulometry measurement shows that the percentage of clay, loam, sand, and gravel in each well tend to differ for every sample. The differences between filled wells and their sediment grain depend on the location of those wells. Maintenance of the wells is required, such as sediment dredging, to rejuvenate them and improve their efficiency.